The Psychology of Leadership Selection: DiSC Results and Leadership Success in Health Care - Fuqua, Ronald M.; Bryan, John (Advances in Social Sciences Research Journal, 2017)
Health care organizations seek successful leaders for their executive positions. Often, a psychologically-based assessment is used in an attempt to recognize factors that cannot easily be seen in applicants during the screening and selection process. There are a variety of assessments available for this purpose, each with its own approach and cost to administer. DiSC is one such instrument used for assessing traits of applicants. Using measures of Dominance, Influence, Steadiness, and Compliance, DiSC is currently used in business settings for the purpose of employee development and team building. Dr. William Marston, a physiological psychologist writing in the 1920s and 1930s, explored the meaning of normal human emotions by relating how a person perceives himself or herself in relation to the environment and describing how the person is likely to behave in response. However, it is questioned whether the assessments used, and the results they produce, can be associated with the success of the leader. In order to address this question, data on the results from the DiSC assessment for a small number of senior leaders of a health care organization is compared to their overall success in that organization. Granted that while the sample is small, 18, and the measures for success are not universal, there is some evidence to study. Other questions that arise are how do the traits of other organizational leaders compare to senior leadership traits, and are these traits indicators of their individual success. Effectively, in terms of success, does it pay to be like the boss or is it better to differ in your traits?